Human Existence (Humanism) Perspective of Hamka's Islamic Philosophy - Hardewita, Mutiara (BELIEF: Sociology of Religion Journal, 2024)
This study aims to describe and analyze the thoughts about human existence or humanism from a figure in the Indonesian Archipelago, namely Haji Abdul Malik Karim Amrullah who is known as Hamka. The method used in this study is the analytical descriptive method. The primary data source used as a reference is a book written by Hamka. The secondary data source comes from books and other journal articles that support this study. Based on the study, it shows that human existence or humanism in Hamka's perspective, where humans are rational is an aspect of humanism. Reason is a guard, and also something that can control humans. Human humanity is reflected in reason that is used optimally. Reason is used by humans to be able to think about how much pleasure humans receive from God. There are three original characteristics found in humans, which are used to perfect the animal nature of humans, namely tendencies, anger, and selfishness.